Sini San Inhibits Chronic Psychological Stress-Induced Breast Cancer Stemness by Suppressing Cortisol-Mediated GRP78 Activation - Zheng, Yifeng; Zhang, Juping; Huang, Wanqing; Zhong, Linda L. D.; Wang, Neng; Wang, Shengqi; Yang, Bowen; Wang, Xuan; Pan, Bo; Situ, Honglin; Lin, Yi; Liu, Xiaoyan; et al. (Frontiers in Pharmacology, 2021)
Chronic psychological stress is closely correlated with breast cancer growth and metastasis. Sini San (SNS) formula is a classical prescription for relieving depression-related symptoms in traditional Chinese medicine (TCM). Current researches have suggested that chronic psychological stress is closely correlated with cancer stem cells (CSCs) and endoplasmic reticulum (ER) stress. This study aimed to investigate the effects of chronic psychological stress on ER stress-mediated breast cancer stemness and the therapeutic implication of SNS. Chronic psychological stress promoted lung metastasis in 4T1 breast tumor-bearing mice and increased the stem cell-like populations and stemness-related gene expression. Meanwhile, GRP78, a marker of ER stress, was significantly increased in the breast tumors and lung metastases under chronic psychological stress. As a biochemical hallmark of chronic psychological stress, cortisol dramatically enhanced the stem cell-like populations and mammospheres formation by activating GRP78 transcriptionally. However, GRP78 inhibitors or shRNA attenuated the stemness enhancement mediated by cortisol. Similarly, SNS inhibited chronic psychological stress-induced lung metastasis and stemness of breast cancer cells, as well as reversed cortisol-induced stem cell-like populations and mammospheres formation by attenuating GRP78 expression. Co-localization and co-immunoprecipitation experiments showed that SNS interrupted the interaction between GRP78 and LRP5 on the cell surface, thus inhibiting the Wnt/β-catenin signaling of breast CSCs. Altogether, this study not only uncovers the biological influence and molecular mechanism of chronic psychological stress on breast CSCs but also highlights SNS as a promising strategy for relieving GRP78-induced breast cancer stemness via inhibiting GRP78 activation.